SELF-REPORTED ESTROGEN USE AND NEWLY-INCIDENT URINARY INCONTINENCE AMONG POSTMENOPAUSAL COMMUNITY-DWELLING WOMEN - Northington, Gina M. (2012)
OBJECTIVE: To examine the relationship between self-reported estrogen use and newly-incident urinary incontinence (UI) among community-dwelling postmenopausal women. METHOD: A population based longitudinal survey of postmenopausal women who did not report UI in 1993 and for whom complete data were available. Women were classified as having newly-incident UI if they reported uncontrolled urine loss within 12 months of the 2004 interview. Condition-specific functional loss secondary to UI was assessed by questions on participants’ inability to engage in certain activities due to UI. Duration of hormone therapy containing estrogen was obtained in 1993 using a structured questionnaire. RESULTS: Among 167 postmenopausal women who did not report UI in 1993, 47 (28.1%) reported newly-incident UI and 31 (18.6%) reported newly-incident UI with condition-specific functional loss in 2004. Of the 167 postmenopausal women, 46 (27.5%) reported ever using hormone therapy containing estrogen and 14 (8.3%) women reported using hormone therapy containing estrogen for 5 years or more in 1993. Estrogen use for 5 years or more was significantly associated with newly-incident UI with condition-specific functional loss compared to estrogen use for less than 5 years or no reported history of estrogen (adjusted relative odds (RO) = 3.97, 95% confidence interval (CI) [1.02, 15.43]) in multivariate models controlling for potentially influential characteristics. CONCLUSIONS: Postmenopausal community-dwelling women with a history of estrogen use for 5 years or more were more likely to report newly-incident UI with condition-specific functional loss after 10 years of follow-up.